RE-Mg-Ni-based AB type electrode alloy for Ni-MH secondary battery and preparation method of RE-Mg-Ni-based AB type electrode alloy
By using RE-Mg-Ni-based AB type electrode alloy and nano-Ni powder mechanical ball milling treatment technology in nickel-hydrogen battery electrode materials, the problem of insufficient electrochemical cycle stability and discharge capacity is solved, and higher electrochemical performance is achieved .
Patent Information
- Application Number
- CN202411645333.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The electrochemical cycling stability and discharge capacity of existing nickel-hydrogen battery electrode materials limit their practical application at room temperature.
Using RE-Mg-Ni-based AB type electrode alloy, the alloying of rare earth elements Ce and metal elements Ni, Co, Al, Mn on the electrode surface, and mechanical ball milling is performed using nano Ni powder to form a dense Ni coating. to improve electrochemical properties.
The electrochemical cycle stability and discharge capacity of the hydrogen storage electrode alloy are significantly improved, so that it has better electrochemical hydrogen storage performance at room temperature.
Smart Images

Figure CN119447275A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen storage alloy materials, and in particular to a RE-Mg-Ni based AB type hydrogen storage electrode alloy for a Ni-MH secondary battery with high capacity and long life, and a preparation method thereof. Background Art
[0002] The main advantages of NiMH batteries are that they are pollution-free, safe, and highly efficient, making them suitable for use in hybrid vehicles. However, further research is needed to improve the performance of NiMH battery systems and reduce their costs in order to increase consumer acceptance of electric or hybrid vehicles.
[0003] Many metal hydrides have been identified as having practical hydrogen storage applications, especially the commercially produced rare earth-based AB5 and AB2 type alloys. However, the specific capacity of AB5 alloy is not ideal and the activation of AB2 alloy is relatively difficult, which limits their further development. Mg-based alloys have good electrochemical hydrogen capacity and are ideal for NiMH battery electrodes. The most attractive advantages of Mg-based alloys are their low cost and high discharge capacity, but the poor electrochemical cycling stability and low discharge capacity of Mg-based alloys limit their practical application at room temperature. Summary of the invention
[0004] The main purpose of the present invention is to provide a RE-Mg-Ni based AB type electrode alloy for Ni-MH secondary battery and a preparation method thereof. Through the present invention, the electrochemical cycle stability of the hydrogen storage electrode alloy is greatly improved while maintaining high capacity.
[0005] Through research on Mg-based alloys, the inventors found that the formation of a thick Mg(OH)2 layer on the electrode surface is the main cause of capacity decay. The newly formed Mg(OH)2 layer inhibits the diffusion of hydrogen and charge transfer, reducing the content of active substances. In addition, harmful pulverization will lead to further corrosion of the active metal and promote the generation of additional Mg(OH)2 during the electrode reaction. Therefore, partial substitution of Mg and / or Ni is considered to be an effective method to improve electrochemical properties, where substitution can enhance the oxidation resistance and / or crushing resistance of alloy electrodes by reducing the expansion coefficient. In particular, the addition of rare earths and transition metals to magnesium-nickel based alloys can improve the corrosion resistance of the alloy and increase the cycle life. Some scholars have studied Mg 0.9− x Ti 0.1 Pd xNi (x = 0.04 - 0.1) alloys, it was found that replacing Mg with Pd greatly improved the electrochemical cycling stability. This improvement was due to the formation of a passivation film on the electrode surface. Some scholars have also reported that adding Pd can improve the cycling stability of Mg2Ni-based alloys and improve the electrochemical performance through surface modification, especially mechanical coating.
[0006] The present invention achieves its object through the following technical solutions.
[0007] On the one hand, the present invention provides a hydrogen storage electrode alloy for Ni-MH secondary batteries, characterized in that the alloy contains rare earth element Ce and metal elements Ni, Co, Al, and Mn, and a certain amount of nano-Ni powder is added, and the surface coating of alloy particles is achieved by mechanical ball milling. Its components are: Mg 10-x Ce x Ni 9-y-z-m Co y Al z Mn m + n wt.%Ni, where x, y, z, m are atomic ratios, and 0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 1, 0 < m ≤ 1, n is the percentage of nano-Ni in the alloy, 40 ≤ n ≤ 60. The preferred atomic ratio x:y:z:m = 1:0.5:0.5:0.5, n = 50.
[0008] On the other hand, the present invention provides a preparation method of a hydrogen storage electrode alloy for Ni-MH batteries, and its preparation steps include:
[0009] 1.配料:按化学式组成Mg 10-x Ce x Ni 9-y-z-m Co y Al z Mn m 进行配料,式中0 < x ≤ 2, 0 < y ≤ 1,0 < z ≤ 1, 0 < m ≤ 1, 其中,所述化学式组成中的Mg在配比时增加8%、稀土Ce及金属Mn在配比时增加5%比例的烧损量,原材料的金属纯度≥99.5%。
[0010] 2. Alloy melting and rapid quenching: The weighed raw materials are melted by conventional heating methods, such as arc melting, induction heating melting or other heating methods. The heating conditions are: evacuating to 1×10-2 - 5×10-5 Pa, introducing high-purity helium gas at 0.01 - 0.1 MPa or a helium + argon mixed gas with a volume ratio of about 1:1 as the protective gas, and the heating temperature is 1500 - 1600 °C to obtain molten Mg 10-x Ce x Ni 9-y-z-m Coy Al z Mn m Liquid master alloy. After the molten alloy is kept in a protective gas atmosphere for about 5 minutes, the liquid master alloy is directly injected into the tundish with an NB nozzle embedded at the bottom. The liquid alloy is continuously sprayed from the nozzle gap of the NB nozzle at the bottom of the tundish (the width of the nozzle gap is 0.3 mm) onto the surface of a water-cooled copper roller rotating at a linear speed of 5-30 m / s to obtain a quenched alloy sheet with a thickness of 50-300 μm. It is necessary to determine the appropriate quenching cooling rate to ensure that the quenched alloy strip has an almost complete nanocrystalline structure with a grain size of 10-100 nm.
[0011] 3. Mechanical ball milling surface coating Ni: Rapid quenching Mg 10-x Ce x Ni 9-y-z-m Co y Al z Mn m The alloy ribbon is mechanically crushed and passed through a 200 mesh sieve. The sieved alloy powder is loaded into a stainless steel ball mill together with a certain amount of nano Ni powder and stainless steel grinding balls. After vacuuming, high-purity argon is filled and ball milled in an all-round planetary high-energy ball mill for 5-20 hours, preferably 8 hours, with a ball-to-material ratio of 20:1 and a rotation speed of 350 rpm. During the ball milling process, the ball mill is shut down for 0.5 hours for every 1 hour of continuous operation to prevent the ball mill and the abrasive from being too hot. The determination of the ball milling time is critical. If the ball milling time is too long, a large amount of amorphous phase will appear, which will reduce the electrochemical properties of the alloy. The optimal ball milling time is to ensure that there is not too much amorphous phase in the ball milled alloy, and to ensure that the nano Ni powder and the alloy powder have a good combination, so that the Ni powder is evenly distributed on the surface of the alloy particles, thereby improving the electrocatalytic activity and cycle stability of the alloy.
[0012] 4. Structural analysis and performance testing: XRD was used to test the phase structure of the as-cast and ball-milled powders, and high-resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM) were used to observe the morphology and microstructure of the as-cast and ball-milled alloys, and selected area electron diffraction (SAED) was used to determine the crystalline state of the alloy. The obtained alloy powder was mixed with carbonyl nickel powder (particle diameter ≤ 2.5 μm) in a mass ratio of 1:4, and then cold-pressed into a cylindrical electrode sheet with a diameter of 15 mm at a pressure of 35 MPa, and then its electrochemical performance was tested using a standard three-electrode test method.
[0013] From ball milled MmMg 12In the process of studying the electrochemical properties of alloy-Ni composite materials, it was found that when the Ni content increased from 150 wt.% to 200 wt.%, the initial discharge increased from 964 mAh / g to 1164 mAh / g. Some scholars have found that the cycle life and maximum discharge capacity of Mg-50 at.% Ni composite materials have been significantly improved. Some scholars have studied the electrochemical properties of Mg2NiH4 prepared by mechanically coating nano-Ni, and the maximum discharge capacity reached 896 mAh / g, and the anti-corrosion ability was significantly improved.
[0014] The application of the technical solution of the present invention has the following technical effects:
[0015] In the present invention, part of Mg is replaced by Ce, and part of Ni is replaced by Al, Co and Mn to improve the electrochemical properties of the alloy. Previous studies have found that the addition of Al and Co can improve the corrosion resistance of AB3 type alloys in KOH electrolytes, and the addition of Ce can significantly improve the electrochemical properties of REMg12 type alloys. On this basis, the alloy surface is modified by nickel powder mechanical coating. The Ni coating effectively increases the corrosion resistance of Mg-based alloys, improves the charge transfer rate on the electrode surface and the diffusion of hydrogen in the electrode. On the basis of scientifically designed components, the Ni coating is coated by melt rapid quenching combined with mechanical ball milling, which not only maintains the high capacity of the alloy, but also greatly improves the electrochemical cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 The SEM morphology of the cast alloys of Examples 1-6.
[0018] Figure 2 This is the rapidly quenched (10 m / s) alloy strip of Example 1.
[0019] Figure 3 The SEM morphology of the ball-milled alloy powders of Examples 1-6.
[0020] Figure 4 The XRD diffraction spectra of the ball-milled powders of Examples 1-6 are shown in FIG.
[0021] Figure 5 HRTEM morphology of the ball-milled powder of Example 1-6. DETAILED DESCRIPTION
[0022] The following will describe the implementation methods of the present application in detail with the help of accompanying drawings and examples, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0023] The present invention has found through research that the pulverization of alloy particles during the process of hydrogen absorption and desorption is the main reason for the decrease in its capacity. Increasing the lattice parameters of the alloy by alloying and reducing the lattice expansion rate during the process of hydrogen absorption and desorption can effectively improve the alloy's anti-pulverization ability, thereby improving the alloy's electrochemical cycle stability. In terms of component design, adding micro-alloying elements Co, Mn and Al can increase the unit cell volume and refine the alloy grains. At the same time, adding multiple rare earth elements Ce to the alloy and matching with Al can significantly improve the corrosion resistance of the alloy elements in the electrolyte, further improving the alloy's electrochemical cycle stability.
[0024] The quenched alloy prepared by vacuum quenching technology has a uniform nanocrystalline-amorphous structure and is arranged in a columnar shape perpendicular to the roller surface. This structure is particularly beneficial to improving the alloy's anti-powdering ability. Unlike ball milling, the ultrafine structure and crystal defects obtained by quenching have high stability. After multiple charge and discharge cycles, the grains are not easy to aggregate and grow. In terms of electrochemical performance, it not only maintains the high capacity of the alloy, but also has good cycle stability. In addition, compared with the casting process, the quenching process completely eliminates the component segregation caused by the crystallization process, which is extremely beneficial to improving the electrochemical properties of the alloy.
[0025] After adding nano-Ni powder and mechanical ball milling, the surface state of the alloy is improved while maintaining the microstructure of the rapidly quenched alloy, giving full play to the respective advantages of the two preparation processes. The surface coating of Ni is the key to the electrochemical hydrogen storage of the alloy in this system. It is well known that RE-Mg-Ni based alloys can basically not electrochemically store hydrogen at room temperature. Even after alloying treatment, their discharge capacity is very low and cannot meet the capacity requirements of the negative electrode of Ni-MH batteries. Through the mechanical coating of nano-Ni powder, the electrocatalytic activity of the alloy surface is fundamentally changed, so that the alloy has good electrochemical hydrogen storage performance at room temperature. At the same time, through the mechanical coating treatment, a uniformly distributed Ni coating is formed on the surface of the alloy particles, which can significantly improve the corrosion resistance of the alloy in alkaline electrolyte, so that the electrochemical cycle stability of the alloy can meet the requirements of the negative electrode of Ni-MH batteries. It is precisely because of the combination of rapid quenching and mechanical ball milling that the electrochemical properties of the alloy are greatly improved.
[0026] The present invention further illustrates the composition and preparation method of the RE-Mg-Ni based AB type electrode alloy involved in the present invention through the following examples.
[0027] The RE-Mg-Ni-based AB-type electrode alloy for Ni-MH batteries of the present invention has a chemical formula of: Mg 10- x Ce x Ni 9-y-z-m Co y Al z Mn m + n wt.%Ni, where x, y, z, m are atomic ratios, and 0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 1, 0 < m ≤ 1, n is the percentage of nano-Ni in the alloy, and 40 ≤ n ≤ 60. The preferred atomic ratio x:y:z:m = 1:0.5:0.5:0.5, and n = 50.
[0028] The preparation method of the RE-Mg-Ni-based AB-type electrode alloy for Ni-MH batteries of the present invention includes the following steps:
[0029] A. Weigh the ingredients according to the chemical formula Mg 10-x Ce x Ni 9-y-z-m Co y Al z Mn m Since metallic Mg, rare earth Ce, and metallic Mn are prone to volatilization, during proportioning, Mg is added at 8% more, and rare earth Ce and metallic Mn are added at 5% more to compensate for the loss by burning.
[0030] B. Place the prepared raw materials in a magnesia crucible in sequence. The massive rare earth Ce is placed at the bottom of the crucible, electrolytic Ni, Co, and Mn are placed on top of the rare earth Ce, electrolytic Al is placed on top of metallic Ni, Co, and Mn, and metallic Mg is placed on the top. After the materials are placed in sequence, cover the furnace lid, evacuate to 1×10 -2 -5×10 -5 Pa, and fill with high-purity helium gas at a pressure of 0.01 - 0.1 MPa as a protective gas. The melting temperature is 1500 - 1600 °C to obtain molten Mg 10-x Ce x Ni 9-y-z-m Co y Al z Mn m liquid master alloy.
[0031] C. Under the protection of inert gas atmosphere, after the alloy is melted and kept warm for about 5 minutes, the liquid master alloy is directly injected into the tundish with the NB nozzle embedded at the bottom. The liquid alloy is continuously sprayed through the slit of the NB nozzle onto the smooth surface of the water-cooled copper roller rotating at 5-30 m / s, preferably 10 m / s, to obtain a quenched alloy sheet with a thickness of 50-300 μm. The quenched alloy has a columnar crystal structure, which is a uniform nanocrystalline structure. The requirement of quenching is to ensure that the quenched alloy strip has as many nanocrystalline structures as possible. If the quenching cooling rate is too fast, a considerable proportion of amorphous phases will appear in the structure, which will cause the electrochemical capacity of the alloy to drop sharply. If the cooling rate is too slow, a large number of microcrystalline structures will appear, weakening the electrochemical kinetics of the alloy.
[0032] D. Rapidly quench Mg 10-x Ce x Ni 9-y-z-m Co y Al z Mn m After the alloy ribbon is mechanically crushed and passed through a 200-mesh sieve, it is mixed with a certain amount of nano-Ni powder and stainless steel grinding balls and loaded into a stainless steel ball mill. After vacuuming, high-purity argon is filled in and ball milled in an all-round planetary high-energy ball mill for 5-20 hours, preferably 8 hours; the ball-to-material ratio is 20:1, and the speed is 350 rpm. During the ball milling process, the ball mill is shut down for 0.5 hours for every 1 hour of continuous operation to prevent the ball mill and the abrasive from being too hot. The RE-Mg-Ni-based AB-type electrode alloy for Ni-MH batteries described in this patent is obtained through the above preparation process. It should be noted that the ball milling process must be appropriate. Too long ball milling time will cause more amorphous phases to appear in the microstructure. At the same time, cold welding between particles will cause agglomeration, which will reduce the electrochemical properties of the alloy. At the same time, too long ball milling time will increase energy consumption and reduce the efficiency of material preparation, which does not meet the requirements of large-scale preparation of alloys.
[0033] E. Use XRD to test the structure of ball-milled powder, use high-resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM) to observe the morphology and microstructure of the alloy before and after ball milling, and use selected area electron diffraction (SAED) to determine the crystalline state of the alloy. Use a simulated battery tester to test the electrochemical discharge capacity and cycle stability of the alloy.
[0034] The chemical composition and proportion of the specific embodiment of the present invention are selected as follows:
[0035] Example 1: Mg9Ce1Ni 7.5 Co 0.5 Al 0.5 Mn 0.5 + 50 wt.% Ni
[0036] Example 2: Mg8Ce2Ni 7.5 Co 0.5 Al 0.5 Mn 0.5 + 50 wt.% Ni
[0037] Example 3: Mg9Ce1Ni7Co1Al 0.5 Mn 0.5 + 50 wt.% Ni
[0038] Example 4: Mg9Ce1Ni7Co 0.5 Al1Mn 0.5 + 50 wt.% Ni
[0039] Example 5: Mg9Ce1Ni7Co 0.5 Al 0.5 Mn1 + 50 wt.% Ni
[0040] Example 6: Mg 8.5 Ce 1.5 Ni 7.5 Co 0.5 Al 0.5 Mn 0.5 + 50 wt.% Ni
[0041] Comparative Example 1: Mg 10 Ni 10 (quick quenching)
[0042] According to the chemical formula composition of each embodiment, block metal Mg, rare earth metal Ce, electrolytic Ni, Co, Mn and Al are selected. The metal purity requirement is ≥99.5%. After the selected block metal is polished to remove the surface oxide layer, it is weighed according to the chemical dosage ratio. Among them, the metal Mg is increased by 8% during the proportioning, and the rare earth Ce and metal Mn are increased by 5% to make up for the burn loss during smelting; during the preparation process, the technical parameters of each stage are as follows: during induction heating, the vacuum is 1×10-2-5×10-4 Pa, and the high-purity helium with a pressure of 0.01-0.1 MPa or a helium + argon mixed gas with a volume ratio of 1:1 is filled; the melting temperature is 1500-1600℃; the surface linear speed of the rapid quenching water-cooled copper roller is 5-30 m / s. After the quick-quenching thin slices are mechanically crushed and passed through a 200-mesh sieve, they are mixed with nano Ni powder and stainless steel grinding balls and loaded into a stainless steel ball milling tank, and ball milled for 5-20 hours using an omnidirectional planetary ball mill, with the ball mill being stopped for 0.5 hours for every 1 hour of continuous operation. All process parameters can be appropriately selected within the above range to prepare the hydrogen storage alloy powder described in the patent. Therefore, although the present invention only cites a typical embodiment, this embodiment is applicable to preparation methods with different parameters.
[0043] Process parameters of Example 1: According to the chemical formula Mg9Ce1Ni 7.5 Co 0.5 Al 0.5 Mn 0.5 , select bulk Mg and rare earth Ce, electrolytic Ni, Co, Mn and Al. The purity of these metals is 99.5%. They are weighed according to the chemical dosage ratio, and each furnace is prepared according to 5 kg of ingredients, including 1358.5 grams of bulk metal Mg, 846.0 grams of rare earth Ce, 2531.4 grams of electrolytic Ni, 165.9 grams of electrolytic Mn, 169.4 grams of electrolytic Co, and 77.6 grams of electrolytic Al. The weighed bulk metal is placed in the magnesium oxide crucible of the medium frequency induction furnace according to the designed process, the bulk rare earth Ce is placed at the bottom of the crucible, the electrolytic Ni, Co and Mn are placed on the rare earth Ce, the electrolytic Al is placed on the metal Ni, Co and Mn, and the metal Mg is placed on the top. Then cover the furnace, evacuate for about 30 minutes to a vacuum degree of more than 5×10-2 Pa, and then fill with high-purity helium protective gas until the pressure reaches 0.04 MPa. Adjust the power to 5 kW and control the temperature at 650℃ to melt the metal Mg. Then adjust the power to 25 kW and control the temperature at 1600℃ to melt the remaining metals. After the molten alloy is kept in the protective gas atmosphere for 5 minutes, the liquid master alloy is directly injected into the tundish with an NB nozzle embedded at the bottom. The liquid alloy is continuously sprayed from the gap between the NB nozzles at the bottom of the tundish (the width of the nozzle is 0.3 mm) onto the surface of the water-cooled copper roller rotating at a linear speed of 10 m / s, and a rapidly quenched alloy sheet with a thickness of about 182 μm is obtained, and the average grain size is about 51 nm. The rapidly quenched Mg9Ce1Ni 7.5 Co 0.5 Al 0.5 Mn 0.5 The alloy flakes were mechanically crushed and passed through a 200-mesh sieve. 20 g of the sieved alloy powder, 10 g of nano-Ni powder and 400 g of stainless steel grinding balls were mixed and loaded into a 250 ml stainless steel ball mill, which was evacuated and sealed after being filled with high-purity argon. The ball mill was milled for 8 hours in an all-round planetary high-energy ball mill. The ball mill was stopped for 0.5 hours for every 1 hour of continuous operation.
[0044] Figure 1 The SEM morphology of the cast alloys of Examples 1-6 shows that after the addition of rare earth Ce and various metal alloys, various intermetallic compounds are formed. Among them, Mg and Ni form Mg2Ni main phase, MgNi2 phase, Ce and Ni form Ce2Ni7 phase, Al and Ni form Al3Ni5 phase and other intermetallic compounds.
[0045] Figure 2This is a photo of the alloy ribbon in the rapid quenching state, with a quenching speed of 10 m / s. The thickness of the test ribbon is about 182 μm. HRTEM observation shows that the alloy ribbon treated by rapid quenching is almost completely nanocrystalline, with an average grain size of about 51 nm.
[0046] Figure 3 The SEM morphology of the ball-milled powder of Examples 1-6 shows that the alloy particles are well dispersed after ball milling and no obvious agglomeration is formed.
[0047] Figure 4 The XRD spectra of the ball-milled alloys of Examples 1-6 show that the ball-milled materials have nanocrystalline and amorphous structural characteristics.
[0048] Figure 5 The HRTEM morphology of the ball-milled alloys of Examples 1-6 shows that the alloys have nanocrystalline and a very small amount of amorphous structure.
[0049] The alloys of the above-mentioned different composition examples were mechanically crushed and passed through a 200-mesh sieve to obtain alloy powders with a diameter of ≤74μm. The alloy powders were mixed evenly with carbonyl nickel powder (particle diameter ≤2.5μm) at a mass ratio of 1:4, and then cold-pressed into cylindrical electrode sheets with a diameter of 15 mm at a pressure of 35MPa, and then their electrochemical properties were tested using a standard three-electrode test method.
[0050] The discharge regime used to test the activation performance and maximum discharge capacity of the alloy is: the charge and discharge current density is 60 mA / g, the charging time is 600 minutes, and the discharge cut-off voltage is -0.5 V; the discharge regime used to test the electrochemical cycle stability of the alloy is: the charge and discharge current density is 300 mA / g, the charging time is 100 minutes, and the discharge cut-off voltage is -0.6 V. When the charge and discharge current density is 300 mA / g, the number of cycles corresponding to the discharge capacity of the alloy dropping to 60% of the maximum discharge capacity is defined as the cycle life of the alloy. S200 is used to represent the retention rate of the alloy capacity after 200 cycles, that is, S200=C200,300 / Cmax,300×100%. Cmax,300-the maximum discharge capacity at a charge and discharge current density of 300 mA / g; C200,300-the discharge capacity after 200 charge and discharge cycles at a charge and discharge current density of 300 mA / g.
[0051] The test results of the alloys prepared in the above examples are listed in Table 1.
[0052] Table 1 Electrochemical properties of the alloys in the examples
[0053] Corresponding embodiment Maximum discharge capacity (mAh / g) <![CDATA[S 200 (%)]]> Cycle life (times) Example 1 577.5 69.8 265 Example 2 510.6 70.4 271 Example 3 521.5 62.5 214 Example 4 533.3 66.2 237 Example 5 538.9 64.9 228 Example 6 564.5 68.9 258 Comparative Example 110.4 - -
[0054] The test results show that the electrochemical performance of the alloy, especially the discharge capacity, is much higher than the rare earth-based AB5 alloy (330mAh / g) currently sold on the market. Compared with similar alloys at home and abroad, the performance of this patented alloy, especially the discharge capacity and electrochemical cycle stability, shows obvious advantages.
[0055] Compared with the conventional RE-Mg-Ni series hydrogen storage alloy and preparation method, the present invention has the following advantages:
[0056] (1) By adding a variety of metal elements to the composition design, microstructure regulation is achieved, thereby improving the discharge capacity and electrochemical cycle stability of the alloy.
[0057] (2) The use of helium protection can basically avoid the volatilization loss of metallic magnesium during induction melting, ensuring that the composition of the prepared alloy meets the designed component molar ratio.
[0058] (3) Compared with the traditional melting and casting + annealing process, the present invention can completely suppress the component segregation of the alloy and obtain a uniform microcrystalline-nanocrystalline-amorphous structure. The hydrogen storage alloy with this structure has strong anti-powdering ability and excellent electrochemical cycle stability.
[0059] (4) Since there is basically no component segregation in the rapidly quenched alloy, annealing treatment can be omitted, saving costs and improving production efficiency. At the same time, the process is easy to master and suitable for large-scale production.
[0060] (5) Mechanical Ni coating treatment greatly improves the electrocatalytic activity of the alloy, making the alloy have a discharge capacity close to the theoretical capacity. Since a relatively dense Ni coating is formed on the surface of the alloy particles, the corrosion resistance of the alloy in alkaline electrolyte is greatly improved, so that the alloy electrode has good electrochemical cycle stability.
[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-capacity and long-life RE-Mg-Ni based AB type hydrogen storage electrode alloy for Ni-MH, characterized in that: Containing multi-transition metal elements Ni, Co, Mn, and Al, and rare earth element Ce, with the composition: Mg 10-x Ce x Ni 9-y-z-m Co y Al z Mn m + n wt.%Ni, where x, y, z, m are atomic ratios, and 0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 1, 0 < m ≤ 1, n is the percentage of nano-Ni powder in the alloy, and 40 ≤ n ≤ 60.
2. The electrode alloy according to claim 1, characterized in that The atomic ratio of the chemical formula is: x: y: z: m = 1: 0.5: 0.5: 0.5, n = 50.
3. A method for preparing a multi-component RE-Mg-Ni based AB type hydrogen storage electrode alloy, characterized in that: The following steps are involved: Step 1: According to the chemical formula Mg 10-x Ce x Ni 9-y-z-m Co y Al z Mn m The ingredients are mixed, where x, y, z, m are atomic ratios, and 0 <x≤2, 0<y≤1, 0<z≤1, 0<m≤1; Step 2: Add the weighed raw materials into the magnesium oxide crucible in order, evacuate to 1× 10-2 to 5×10-5Pa, then fill with protective gas with a pressure of 0.01 to 0.1 MPa, and heat to 1500-1600℃ by induction heating to obtain molten Mg 10-x Ce x Ni 9-y-z-m Co y Al z Mn m Liquid alloy.
4. Step 3: Inject the liquid master alloy prepared in the above step 2 directly into the tundish with a BN nozzle embedded at the bottom. The liquid alloy is continuously sprayed onto the smooth surface of the rotating copper roller through the narrow gap of the BN nozzle at the bottom of the tundish to obtain a quick-quenched alloy thin strip with a thickness between 50-300 μm. The quick-quenched strip has a nanocrystalline structure and a grain size of 10-100 nm.
5. Step 4: The rapidly quenched Mg obtained in step 3 10-x Ce x Ni 9-y-z-m Co y Al z Mn m The alloy is mechanically crushed and screened, and the sieved alloy powder, nano-Ni powder and stainless steel grinding balls are loaded into a stainless steel ball mill, which is then evacuated and filled with high-purity argon gas. The mixture is ball milled in an omnidirectional planetary high-energy ball mill to obtain a powdered hydrogen storage electrode alloy.
6. The method for preparing the hydrogen storage electrode alloy according to claim 3, characterized in that: In step 1, the atomic ratio is: x: y: z: m = 1: 0.5: 0.5: 0.5, n = 50.
7. The method for preparing the hydrogen storage electrode alloy according to claim 3, characterized in that: In the step 2, the protective gas is high-purity helium or a mixed gas of helium and argon in a volume ratio of 1:
1.
8. The method for preparing the hydrogen storage electrode alloy according to claim 3, characterized in that: In the step three, the copper roller rotates at a linear speed of 5-30 m / s (preferably 10 m / s).
9. The preparation method according to claim 3, characterized in that: In step 4, ball milling is performed in an omnidirectional planetary high-energy ball mill for 3-10 hours, with a ball-to-material ratio of 20:1 and a rotation speed of 350 rpm. During the ball milling process, the ball mill is stopped for 0.5 hour for every continuous operation of 1 hour.
Citation Information
Patent Citations
RE-Mg-Ni-Ti-Cu-Al-B series AB type electrode alloy used for Ni-MH battery and preparation method
CN105895888A
Method for modifying La-Mg-Ni based hydrogen storage alloy through n-heptanal p-phenylenediamine bis-schiff base
CN106001546A
Anode catalyst of direct borohydride fuel cell and preparation method thereof
CN111952609A
RE-Mg-Ni series three-element or more system hydrogen-storage alloy and amorphous preparing method thereof
CN1528939A
High-capacity rare earth-magnesium based multi-phase hydrogen strage alloy for MH-Ni battery and its preparation method
CN1754972A